1999
DOI: 10.1590/s0100-879x1999000700014
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene-mediated downregulation of RECK, a novel transformation suppressor gene

Abstract: The RECK gene was initially isolated as a transformation suppressor gene encoding a novel membrane-anchored glycoprotein and later found to suppress tumor invasion and metastasis by regulating matrix metalloproteinase-9. Its expression is ubiquitous in normal tissues, but undetectable in many tumor cell lines and in fibroblastic lines transformed by various oncogenes. The RECK gene promoter has been cloned and characterized. One of the elements responsible for the oncogene-mediated downregulation of mouse RECK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
(24 reference statements)
0
20
0
2
Order By: Relevance
“…DAB2 is of particular interest since it suppresses signaling from the growth factor signal transduction pathway to AP-1 (33,104) and is down regulated in a variety of human tumors (11,23). Other known tumor suppressor genes, those for thrombospondin 1 (63,78), RECK (69,81,99), TIMP1 (77), IGSF4 (25), gremlin/ CKTSF1B1 (10), sFRP1 (49,98), IGFBP7/MAC25 (96), fibronectin 1 (52,73,101), STAT1 (38), and FAT (21), and some purported tumor suppressor genes, those for brush-1/WASF3 (87), TES (102), and WNT5A (39), are all down-regulated in Tif-Fos cells. The number of tumor suppressor genes that are down-regulated in Tif-Fos cells and their breadth of activities (ECM components, transcription regulators, signal transducers, and protease inhibitors) reflect the complexity of the invasion program and the many aspects of cell biology that are engaged during invasion.…”
Section: Discussionmentioning
confidence: 99%
“…DAB2 is of particular interest since it suppresses signaling from the growth factor signal transduction pathway to AP-1 (33,104) and is down regulated in a variety of human tumors (11,23). Other known tumor suppressor genes, those for thrombospondin 1 (63,78), RECK (69,81,99), TIMP1 (77), IGSF4 (25), gremlin/ CKTSF1B1 (10), sFRP1 (49,98), IGFBP7/MAC25 (96), fibronectin 1 (52,73,101), STAT1 (38), and FAT (21), and some purported tumor suppressor genes, those for brush-1/WASF3 (87), TES (102), and WNT5A (39), are all down-regulated in Tif-Fos cells. The number of tumor suppressor genes that are down-regulated in Tif-Fos cells and their breadth of activities (ECM components, transcription regulators, signal transducers, and protease inhibitors) reflect the complexity of the invasion program and the many aspects of cell biology that are engaged during invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular matrix (ECM) turnover is clearly involved during palatogenesis events, and matrix metalloproteinases (MMPs) play a critical role during this process (MorrisWiman et al 1999;Mansell et al 2000;Blavier et al 2001;Brown et al 2002;Shi et al 2008). On the other hand, a novel endogenous inhibitor of MMPs has been discovered (Sasahara et al 1999a(Sasahara et al , 1999b(Sasahara et al , 2002; products of the RECK gene (reversion-inducing-cysteine-rich protein with Kazal motifs) were first identified by inducing phenotype reversion in mice fibroblasts (NIH-3T3) transformed by Ras (v-KiRas). Current work has revealed that RECK is widely expressed in normal human and mouse tissues (Nuttall et al 2004;Takahashi et al 1998;Accorsi-Mendonça et al 2008;Zambuzzi et al 2009a;Paiva et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression of RECK gene is seen in human and mouse tissues, opposed to tumoral cell lines where RECK expression is rather low (Nuttall et al 2004). Evidences suggest that RECK is an invasion and metastasis-suppressor gene, whose downregulation by oncogenic signals contribute to the manifestation of the malignant phenotype, being negatively regulated by oncogenes, such as ras and myc (Noda et al 2003;Sasahara et al 1999aSasahara et al , 1999bTakahashi et al 1998). Recently, RECK has being considered a promising prognostic marker and potential therapeutic agent in multiple cancers (Clark et al 2007).…”
Section: Introductionmentioning
confidence: 99%